Common Variable Immunodeficiency and Other Immunodeficiency Syndromes in Bronchiectasis - McShane, Pamela J. (Seminars in Respiratory and Critical Care Medicine, 2021)
Immunodeficiency represents a vast number of diseases and syndromes. Both primary and secondary forms of immunodeficiency are important contributors to the development of bronchiectasis. Primary immune deficiencies, in particular, are increasingly identified and defined as contributors. Specific immune deficiencies that are closely associated with bronchiectasis and as discussed in this article are common variable immunodeficiency, specific antibody deficiency, immunodeficiencies involving immunoglobulin E, DOCK8 immunodeficiency, phosphoglucomutase 3 deficiency, activated phosphoinositide 3-kinase delta syndrome, and X-linked agammaglobulinemia. Each of these primary immune deficiencies has unique nuances. Vigilance for these unique signs and symptoms is likely to improve recognition of specific immunodeficiency in the idiopathic bronchiectasis patient. Secondary forms of immunodeficiency occur as a result of a separate disease process. Graft versus host disease, malignancy, and human immunodeficiency virus are three classic examples discussed in this article. An awareness of the potential for these disease settings to lead to bronchiectasis is necessary to optimize patient care. With understanding and mindfulness toward the intricate relationship between bronchiectasis and immunodeficiency, there is an opportunity to elucidate pathophysiologic underpinnings between these two syndromes.
Keywords: common variable immunodeficiency disorders; bronchiectasis; primary immunodeficiency; secondary immunodeficiency; pulmonary disease